Enhancing Understanding of Community and Public Health. Issue 4 (July 2017) - Kim, Richard W.; Nahar, Vinayak K.
Introduction to Community and Public Health presents the essentials of community and public health and uses the diverse, real-world experiences of the authors to provide practical and memorable understandings of major concepts and principles. It is straightforward and easy to read with frequent examples and scenarios along with focus features in each chapter that describe interesting discoveries or applications that keep the reader captivated. This practical overview provides 545 valuable pages outlining the essentials of community and public health. Students, health educators, and practitioners at all levels will find this book to be a well–thought out, convenient, and effective resource in the classroom and beyond. The application of well-established principles and contemporary knowledge alike make this textbook a strong contribution to the educational and professional literature.